Relações de interatividade dos leitores do diário gaúcho com o meio online - Cunha, Karen Sica da (2011)
The media has changed due to the emergence of new technologies. Traditional media has segmented the content to meet the demand of the population. The popular newspapers were created, reaching readers who did not use to buy printed papers because of the high cost. With a peculiar language, bold colors and eye-catching headlines, such publications caught the attention of part of a less favored population. With the advances in technology, popular journalism has also changed, following the natural order and also gaining ground in the online medium. Diário Gaúcho , a popular publication in the state of Rio Grande do Sul, which covers readers from classes "B", "C" and "D" will be analyzed in this academic research in order to show how the popular journalism on the Internet happens. In addition, the readers interactivity relationships of this popular newspaper with the web will be observed. A few years ago, these readers had no access to the network, but due to the increasing purchasing power, they started standing out as one of the classes of higher growth in the Brazilian market. It is clear, then, that class C seeks information in the online medium and contributes to the means by sending content to the popular papers on the web.